Antiseptic Gel Formulation Uses Eco-Enzyme from Rambutan (Nephelium lappaceum) Peels Substitute the Active Ingredient Alcohol : Formulasi Gel Antiseptik Menggunakan Eco-Enzyme Dari Kulit Buah Rambutan (Nephelium lappaceum) Untuk Mensubstitusi Bahan Aktif Alkohol - Razak, Abd. Rahman; Maqnalia, Maura Maqnalia; Lauende, Sarah Hapritasya; Ainun, Sri; Setiawan, Muh. Risky (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2025)
Background: Eco-enzyme is the result of fermenting organic waste that possesses antibacterial properties. Objectives: This research aims to develop the best formula for an environmentally friendly antiseptic gel. Methods: The analysis carried out in this research includes testing the physical parameters and antibacterial activity of preparation. Results: The liquid eco-enzyme product produced has a distinct strong acid aroma with a pH of 3.1. Antiseptic gels were created in five formulations (F1-F5) by substituting the active alcohol ingredient traditionally used as an antibacterial agent. Test results showed that F1, F2, and F3 met all the requirements for the physical parameters of the gel, including pH (4.5-6.5), viscosity (2000-4000 Cp), spreadability (5-7 cm), and homogeneity (homogeneous). Meanwhile, F4 did not meet the physical parameter of viscosity, and F5 did not meet the parameters for viscosity and spreadability. Antiseptic gel made from eco-enzyme extracted from rambutan fruit peels exhibited higher antibacterial activity against S. aureus and E. coli bacteria compared to two commercial antiseptic gels and F1, which served as the negative control. Conclusion: An antiseptic gel preparation containing rambutan peel eco-enzyme with a concentration of 50% and 50% alcohol (F3) is the best formula.